2022
DOI: 10.3390/ijerph19095717
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver Characteristics of Adults with Acute Traumatic Brain Injury in the United States and Latin America

Abstract: Objectives: To compare characteristics of caregivers of adults with acute traumatic brain injury (TBI) in the U.S. and Latin America (Mexico and Colombia). Design: Secondary data analysis of two cohorts. Cohort 1: English-speaking caregivers of adults with TBI in the U.S. (n = 80). Cohort 2: Spanish-speaking caregivers of adults with TBI in Mexico or Colombia (n = 109). Results: Similarities between the U.S. and Latin American caregiver groups, respectively, were: predominantly women (81.3%, 81.7%, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 60 publications
(72 reference statements)
0
1
0
Order By: Relevance
“…The same authors also found that cognitive impairments and global disability (as measured with the Glasgow Outcome Scale-Extended) were significantly predictive of both subjective and objective burden. Care partner burden (again for younger adults sustaining TBI) has been shown to be associated with a variety of factors including the care partner’s preinjury health status (Davis et al, 2009) and sociocultural or socioeconomic background (Juengst et al, 2022; Sander et al, 2019). There is however very little literature available on care partner burden of older adults with TBI.…”
mentioning
confidence: 99%
“…The same authors also found that cognitive impairments and global disability (as measured with the Glasgow Outcome Scale-Extended) were significantly predictive of both subjective and objective burden. Care partner burden (again for younger adults sustaining TBI) has been shown to be associated with a variety of factors including the care partner’s preinjury health status (Davis et al, 2009) and sociocultural or socioeconomic background (Juengst et al, 2022; Sander et al, 2019). There is however very little literature available on care partner burden of older adults with TBI.…”
mentioning
confidence: 99%